Proposta de um modelo de mensuração do impacto de indicadores de desenvolvimento de mercado - Gerhardt, Vinícius Jaques (2020)
The changes in society's behavior caused different market demands that intensified the competitiveness between organizations. Since market development strategies and actions play a fundamental role in attracting and retaining consumers, it appears that these generate a direct influence on the companies' financial results. In addition to creating and improving market development strategies and actions, carrying out procedures that measure the impact caused by these techniques is also necessary. The performance indicators, in turn, are monitoring variables that help in decision making and the preparation of action plans, so that they play an important role in measuring companies' performance. Thus, this study aims to propose a model for measuring the impact of market development indicators. After conducting systematic reviews that supported the main information for the execution of the research, a theoretical proposal of performance indicators was elaborated grouped in stages that segment the market development process. The theoretical proposal was validated by specialists in the market development area, according to the development of a research instrument that addressed the issues of acceptance or denial of the proposed steps and indicators. As soon as the proposal was ratified, the measurement model was applied in a company in the non-alcoholic beverages sector, in which the market development managers answered the questions regarding the ranking and the relationship between the established indicators. The MONNA software processed these responses and helped to measure the indicators. Consequently, the measurement results were evaluated. The study collaborates with existing research and provides a model that guides companies in their decisions and actions, so that it identifies the market development indicators most present in the current literature, dividing them into stages that represent the chronological order of the process market development.